2002
DOI: 10.1523/jneurosci.22-13-05321.2002
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Mechanisms of Disinhibition Produced by GABAAReceptor Mutations Linked to Epilepsy in Humans

Abstract: The first mutations of the GABA(A) receptor channel linked to familial epilepsy in humans were reported recently (Baulac et al., 2001; Wallace et al., 2001). Preliminary functional analysis of alpha1beta2gamma2 GABA(A) receptors expressed in Xenopus oocytes suggested that the gamma2 subunit R43Q mutation abolished current enhancement by the benzodiazepine, diazepam, and that the gamma2 subunit K289M mutation decreased current amplitudes. We used single-channel recording and concentration jump techniques applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
135
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 27 publications
20
135
3
Order By: Relevance
“…Our results suggest that either of these changes in subunit expression would slow the deactivation rate. In addition, two GABAR mutations associated with inheritance of epilepsy have been found to accelerate the deactivation rate, also correlating rapid deactivation with conditions of hyperexcitability (Bianchi et al, 2002b;Fisher, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that either of these changes in subunit expression would slow the deactivation rate. In addition, two GABAR mutations associated with inheritance of epilepsy have been found to accelerate the deactivation rate, also correlating rapid deactivation with conditions of hyperexcitability (Bianchi et al, 2002b;Fisher, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…It is not likely that the ␤ 2 subunits detected on the cell surface are incorporated into anything other than pentamers, as previous studies have shown that partially assembled receptor intermediates containing ␣␥, ␣␤, or ␤␥ subunits are not expressed on the cell surface (19). In electrophysiological studies (14,15), GABA-evoked currents were measured from HEK 293 cells co-expressing wild-type ␣, ␤, and mutant ␥ 2 R43Q subunits, indicating expression of some ␤ 2 subunit containing receptors on the cell surface. Our data, however, suggest a decrease in surface GABAR protein in cells expressing the mutant ␥ 2 R43Q subunit compared with cells expressing WT subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant receptor expression in HEK 293 cells combined with patchclamping and rapid drug application techniques demonstrated that the ␥ 2 R43Q mutation slowed GABAR deactivation and speeded desensitization (14). In contrast, another study using expression in HEK 293 cells and similar recording techniques reported no differences in receptor kinetics or diazepam potentiation of GABA current between mutant and WT receptors but instead observed reductions in maximal GABA-induced current in cells expressing mutant receptors (15).…”
mentioning
confidence: 99%
“…1,[4][5][6][7][8]14 The N40S mutation identified in this study affects a highly conserved Asn at residue 40 of the mature g2 subunit, thus, the mutation is adjacent to the first one of the two high-affinity benzodiazepine-binding domains of the g2 subunit (Lys-41-Trp-82 in the mature g2 subunit). Wallace et al 15 had suggested that R43Q mutation in the benzodiazepine-binding site can attenuate benzodiazepine sensitivity of GABA A receptor. Another study on this mutation was shown to accelerate deactivation of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Several subsequent studies have identified the retention of mutant receptors in the ER 14 and shown that GABRG2 mutations have reduced trafficking either to the membrane surface with relatively normal function 18,19 or to the surface with impaired function. 15,20 It is believed that the main electrophysiological deficit of GABA A receptor resulting from the mutation is due to intracellular trafficking abnormality of channel molecules. Thus, the N40S mutation may result in an aberrant trafficking of the GABA A receptor.…”
Section: Discussionmentioning
confidence: 99%